2020
DOI: 10.1371/journal.pone.0240158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 90 g/day low-carbohydrate diet on glycaemic control, small, dense low-density lipoprotein and carotid intima-media thickness in type 2 diabetic patients: An 18-month randomised controlled trial

Abstract: This study explored the effect of a moderate (90 g/d) low-carbohydrate diet (LCD) in type 2 diabetes patients over 18 months. Methods Ninety-two poorly controlled type 2 diabetes patients aged 20-80 years with HbA1c �7.5% (58 mmol/mol) in the previous three months were randomly assigned to a 90 g/d LCD r traditional diabetic diet (TDD). The primary outcomes were glycaemic control status and change in medication effect score (MES). The secondary outcomes were lipid profiles, small, dense low-density lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 26 publications
(54 reference statements)
0
40
0
Order By: Relevance
“…The majority of controlled lifestyle (including diet and/or exercise) interventions have failed to demonstrate a clear effect on ccIMT compared to control (24,49), while only one of these unsuccessful studies reported a subgroup analysis with highrisk participants (50). However, some controlled trials using diet and/or exercise have been able to show a favourable effect on ccIMT (decrease or slowed progression), and when dietary recommendations were given, these included advice to adhere to a traditional Mediterranean diet (which is a plant-based dietary pattern) (51,52) or to consume less salt and alcohol and more fruit and vegetables (53), and in one study, more dairy (20) (all randomized controlled trials).…”
Section: Comparison With Results From the Literaturementioning
confidence: 99%
“…The majority of controlled lifestyle (including diet and/or exercise) interventions have failed to demonstrate a clear effect on ccIMT compared to control (24,49), while only one of these unsuccessful studies reported a subgroup analysis with highrisk participants (50). However, some controlled trials using diet and/or exercise have been able to show a favourable effect on ccIMT (decrease or slowed progression), and when dietary recommendations were given, these included advice to adhere to a traditional Mediterranean diet (which is a plant-based dietary pattern) (51,52) or to consume less salt and alcohol and more fruit and vegetables (53), and in one study, more dairy (20) (all randomized controlled trials).…”
Section: Comparison With Results From the Literaturementioning
confidence: 99%
“…Measurement of HbA1c provides a much more complete picture of glycemia than one-time fasted or fed glucose measurement and is indicative of inadequate insulin secretion or glucose uptake over time. Impressively, studies in patients with T2DM on LCD and KD both randomized and non-randomized, controlled and uncontrolled trials, from 2 weeks to 44 months reproducibly resulted in decreased HbA1c [ 69 , 71 , 72 , 75 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Similarly, case studies of varying lengths tended to also find improvements in HbA1c after 20 weeks [ 87 ].…”
Section: Islet Hormone Secretionmentioning
confidence: 99%
“…Similarly, case studies of varying lengths tended to also find improvements in HbA1c after 20 weeks [ 87 ]. Controlled studies have found this improvement in HbA1c on LCD and KDs compared against diets with the majority of energy coming from carbohydrates, diets with low glycemic index and calorie restriction, and caloric restriction alone [ 69 , 79 , 81 , 84 ]. In addition, continuous care regimens using KDs have be shown to greatly improve HbA1c in patients with T2DM compared to current standard T2DM care [ 88 , 89 ].…”
Section: Islet Hormone Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some healthy foods are eaten on a ketogenic diet, for example, seafood, low-carb vegetables, cheese, eggs, meat, poultry, coffee, and tea. The importance of high fat in aging-related sarcopenic obesity reducing regimens on different metabolic models are shown by comparing the effects of four different types of ketogenic dietary regimens [3,4]. Standard ketogenic diet (SKD): This typically contains a very low, only 5% carbohydrate, 15% moderate proteins, 80% high fat diet.…”
Section: Introductionmentioning
confidence: 99%